CIMA P1 Management Accounting Study Text - CIMA astranti (Wiltshire, UK Astranti, 2019)
The Astranti Study Texts have been used by thousands of CIMA Students in preparation for their management accountancy exams. They cover the entire CIMA syllabus for the 2015 exams and onwards and have been carefully written to be concise and easy to read but detailed enough to clearly guide you through the topics you must know in order to pass the exams. What are you waiting for? Download the sample of the book to see one for yourself. Prepared by our expert team of professional writers the study texts feature: Full Syllabus Coverage Clear and simple explanations for ease of understanding Carefully worked step-by-step examples Condensed and focused on likely exam content
Keywords: Nonfiction; Management Accounting